Analisis Strategi Pengembangan Destinasi Wisata Berdasarkan Komponen 6A Di Taman Wisata Guci Tegal, Jawa Tengah - Anggriani, Lusianty; Rosanto, Stephanie (CV RIFAINSTITUT, 2023)
This research was conducted with the aim of analyzing the 6A component (Attraction, Amenities, Accessibilities, Activity, Ancillary, Available Package) at Taman Wisata Guci. This study uses qualitative research methods with observation and interview data collection techniques. The analysis technique used is triangulation, SWOT analysis (Strength, Weakness, Opportunity, Threats) and SWOT Matrix. The results of the study show that there are still 6A components in Guci Tourism Park that are not optimal, such as amenities and accessibility, but other components, namely attractions, ancillaries, activities, and available packages can be further improved for the convenience of visitors. tourist.